Implementasi Metode Fuzzy Analytic Hierarchy Process (F-AHP) Dalam Penentuan Peminatan di MAN 2 Kota Serang - Muhammad Fajri; Rekyan Regarsari Mardhi Putri; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Specialization programs are introduced as an effort to better lead students based on their talents, interests, and academic abilities. There are four groups of specialization in Madrasah Aliyah Negeri 2 Kota Serang, namely IPA, IPS, Language, and Religion. The specialization of IPA is for students who have a tendency in the science of certainty. IPS specialization is for students with social science tendencies. Language specialization is for students who have a tendency to speak the language. And religious interest is for students who have religious inclination. In the determination of student interest, MAN 2 Kota Serang uses five aspects of specialization such as the value of acceptance of new learners (PPDB), the value of national examination, the value of report cards, the results of psychological tests, and ask students. But in the determination of specialization there is no standardization of weighting in every aspect of specialization so that the results obtained are not maximal. Fuzzy Analytical Hierarchy Process (F-AHP) is able to overcome the weaknesses in criteria that have more subjective properties on the AHP method. Fuzzy logic itself is a logic that has a value of disguise between two values. In this study, the resulting accuracy is 76.67% with 30 test data for the determination of specialization in MAN 2 Kota Serang.